Parent-child attachment mediates the association between parental conflict perceptions and suicide intention: a cross-sectional survey among middle school students in China - Wang, Jiana; Chen, Kun; Huang, Xinyuan; Jin, Zhiyu; He, Jing; Han, Bingsong; Feng, Lin; Meng, Nana; Yang, Cong; Yao, Pin; Li, Zhe (Frontiers in Public Health, 2024)
Introduction Adolescent suicide is a prevalent issue globally, with various factors contributing to this phenomenon. This study aimed to investigate these factors and their interrelationships to better understand the causes of adolescent suicide and provide evidence for its prevention. Methods This study conducted among middle school students in Liaoning Province, China, from April to May 2016, A cross-sectional survey was administered to 1,028 students aged 10–19, using instruments such as the Behavior Questionnaire-Revised (SBQ-R), Children's Perception of Interparental Conflict Scale (CPIC), and revised version of Inventory of Parent Attachment (IPPA-R). Result Binary logistic regression analysis revealed that adolescents aged 15–19, adolescents with strong perceptions of parental conflict were at high risk of suicide intention. Adolescents living in rural areas, adolescents with high mother-child attachment, adolescents with high father-child attachment were at low risk of suicide intention. Furthermore, parent-child attachment played a mediating role between two dimensions of parental conflict perception (resolved situations and response effect) and suicide intention. Discussion The study concludes that adolescents living in urban areas, older adolescents, adolescents with a high level of parental conflict intensity, and those with low levels of parent-child attachment are at high risk of suicide intention. parent-child attachment played a mediating role between two dimensions of parental conflict perception (resolved situations and response effect) and suicide intention. Interventions aimed at reducing family conflicts and improving parent-child relationships are recommended to decrease the incidence of adolescent suicide.